Expression of the Iron Hormone Hepcidin Distinguishes Different Types of Anemia in African Children - Pasricha, S-R; Atkinson, SH; Armitage, AE; Khandwala, S; Veenemans, J; Cox, SE; Eddowes, LA; Hayes, T; Doherty, CP; Demir, AY; Tijhaar, E; Verhoef, H; et al. (American Association for the Advancement of Science, 2014)
Childhood anemia is a major global health problem resulting from multiple causes. Iron supplementation addresses iron deficiency anemia but is undesirable for other types of anemia and may exacerbate infections. The peptide hormone hepcidin governs iron absorption; hepcidin transcription is mediated by iron, inflammation, and erythropoietic signals. However, the behavior of hepcidin in populations where anemia is prevalent is not well established. We show that hepcidin measurements in 1313 African children from The Gambia and Tanzania (samples taken in 2001 and 2008, respectively) could be used to identify iron deficiency anemia. A retrospective secondary analysis of published data from 25 Gambian children with either postmalarial or nonmalarial anemia demonstrated that hepcidin measurements identified individuals who incorporated >20% oral iron into their erythrocytes. Modeling showed that this sensitivity of hepcidin expression at the population level could potentially enable simple groupings of individuals with anemia into iron-responsive and non-iron-responsive subtypes and hence could guide iron supplementation for those who would most benefit.